Nitrate reductase activity in leaves and stems of tanner grass (Brachiaria radicans Napper) - Cazetta, Jairo Osvaldo [UNESP]; Villela, Luciana Cristine Vasques [UNESP] (Universidade de São Paulo (USP), Escola Superior de Agricultura Luiz de Queiroz (ESALQ), 2004)
A 'tanner grass' (Brachiaria radicans Napper) é uma planta forrageira que se adapta bem tanto em solos bem drenados como em encharcados, e responde bem à adubação nitrogenada. A assimilação do nitrogênio (N) envolve a enzima nitratro redutase (NR) cuja atividade é dependente do suprimento de N. O Molibdênio (Mo) também é importante por ser um co-fator da RN. Neste trabalho foi otimizado um procedimento para a determinação da atividade da redutase do nitrato (NRA) in vivo para tecidos de folha e caule. Este método foi aplicado para avaliar plantas fertilizadas com NaNO3, NH4Cl ou uréia, com e sem a aplicação de H2MoO4, visando contribuir no balizamento da adubação nitrogenada para esta espécie. As melhores condições para a determinação da NRA foram: incubação de 300 mg de tecidos em um meio composto por tampão fosfato 200 mmol dm3 (pH 7,4); KNO3 60 mmol dm3; n-butanol 10 cm³ dm3; triton-x-100® 0,1 cm³ dm3; infiltração a vácuo no escuro; por período de 60 a 100 minutos. As folhas apresentaram NRA duas a três vezes maior que os caules. A matéria fresca do caule e a NRA não foi afetada pelas fontes de N. As plantas adubadas com NaNO3, NH4Cl e uréia apresentaram, respectivamente, os maiores, os menores e intermediários crescimento e NRA. A aplicação de Mo na ausência de N aumentou a NRA e não afetou o crescimento, mas, na presença de N, limitou a NRA nas folhas e o crescimento das plantas.

Tanner grass (Brachiaria radicans Napper) is a forage plant that is adapted to well-drained soils or wetlands, and responds well to nitrogen (N) fertilization. The assimilation of N involves the nitrate reductase (NR) enzyme, and its activity seems to be dependent on N supply. Molybdenum (Mo) is also important because it is a cofactor of NR. In this study, the variables of an in vivo assay were optimized for measuring nitrate reductase activity (NRA) in the leaves and stem tissues. This method was used to evaluate NO3- metabolism in plants fertilized with NaNO3, NH4Cl or urea, in association with or without application of H2MoO4, aiming to provide guidelines for N management of this species. The best conditions to determine NRA involved the incubation of 300 mg of tissues in a medium composed of 200 mmol dm3 phosphate buffer (pH 7.4), 60 mmol dm3 KNO3, 10 cm³ dm3 n-butanol, 0.1 cm³ dm3 detergent (triton-X-100®), under vacuum and in the dark for a period of 60 to 100 minutes. Leaves showed NRA levels two to three times higher than stems. Although there were some interactions between treatments, stem fresh weight and NRA were not affected by N sources. Plants fertilized with NaNO3 showed the best growth and NRA values when compared with NH4Cl and urea, which had, respectively, the lowest and intermediate scores. The application of Mo in the absence of N improved NRA and did not affect leaf and stalk growth. In the presence of N, the Mo levels applied limited leaf NRA and plant development.
Atividade da redutase do nitrato em folhas e caules de 'tanner grass'(Brachiaria radicans Napper)
Keywords: Brachiaria arrecta; Nitrogen; molybdenum; enzyme; Brachiaria arrecta; Nitrogênio; molibdênio; enzima